Atrial fibrillation in the military patient: a review. Issue 3 (5th August 2015) - Hunter, Alys H; Cox, AT; D'Arcy, J; Rooms, M; Camm, AJ
Abstract : Atrial fibrillation (AF) is the most common sustained atrial arrhythmia, and increases an individual's risk of morbidity and mortality from cardiovascular and thromboembolic events. In this article, we review the pathophysiology and clinical presentations of AF and describe appropriate investigations and management likely to be appropriate for a military population, in line with current National Institute for Health and Care Excellence and European Society of Cardiology guidelines. The implications for the individual's Medical Employment Standard in the UK Armed Forces, with specific reference to specific military occupational activities such as aviation, diving and driving occupationally, are also reviewed.